2016
DOI: 10.1002/pits.21975
|View full text |Cite
|
Sign up to set email alerts
|

Academic Self‐efficacy Among Junior High School Students in Ghana: Evaluating Factor Structure and Measurement Invariance Across Gender

Abstract: Self-efficacy is a universal construct, but few validated measures exist for researchers in developing countries to use in assessing youths' perceptions of their ability to achieve academic success. This study examined the cross-cultural suitability and psychometric properties of an academic selfefficacy scale (ASES) adapted for the Ghanaian context. ASES construct validity was assessed with a sample of 4,289 Ghanaian junior high-school students and exploratory and confirmatory factor analysis. Invariance test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The revised response options ranged from cannot do at all (= 0) to moderately can do (= 5) to highly certain can do (=10). Given that the scale has been validated for use in Ghana in a psychometric study (Ansong, Rabiner, Masa, & Chowa, 2016), we used the linear combination method to create an academic self-efficacy index. The Cronbach's alpha for the scale was 0.74 (Ansong et al, 2016).…”
Section: Instrumentmentioning
confidence: 99%
“…The revised response options ranged from cannot do at all (= 0) to moderately can do (= 5) to highly certain can do (=10). Given that the scale has been validated for use in Ghana in a psychometric study (Ansong, Rabiner, Masa, & Chowa, 2016), we used the linear combination method to create an academic self-efficacy index. The Cronbach's alpha for the scale was 0.74 (Ansong et al, 2016).…”
Section: Instrumentmentioning
confidence: 99%
“…The general self-efficacy scale developed by Jerussalem and Schwarzer was tested by Sholz et al (2002) for 25 countries and they found it as unidimensional. Ansong et al (2016) also tested the unidimensional structure of the academic self-efficacy scale developed by Muris (2001) for Ghana and emphasized that the academic self-efficacy structure is a property measured in unidimensional. The researchers, who use the PISA data, may accept the academic self-efficacy as a unidimensional structure.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the conceptualization of Byrne et al (2014), academic self-efficacy represents students' confidence in their ability to perform such academic activities as: (1) asking questions, (2) responding to questions, (3) approaching teachers for help, (4) engaging in academic discussions, (5) following and making sense of material covered in class, (6) meeting assignment and project deadlines, (7) consulting friends for help, (8) producing best work in exams, (9) making sense of feedback from teachers on assignments, (10) being able to study independently, and (11) passing the semester in the first attempt. Note, that these academic activities are also appropriate for determining academic self-efficacy in the context of online classes, as the conceptualization of academic self-efficacy by Byrne et al (2014) represents the construct more adequately than other academic selfefficacy scales (e.g., Alegre, 2014;Ansong et al, 2016;Dullas, 2018). Research indicates that academic selfefficacy has a direct effect on academic achievement (Hayat et al, 2020).…”
Section: Academic Self-efficacymentioning
confidence: 99%